Hygrothermal Effect on Glass Fiber Reinforced Plastic (GFRP) Under Seawater Immersion - Sutjiadi, Adrian (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2024)
Glass Fiber Reinforced Plastic (GFRP) is extensively used for corrugated roofing sheets and gutters in Indonesia, especially in corrosive environments, due to its superior corrosion resistancecompared to steel. Despite its widespread application in coastal areas, limited studies have examined the durability of GFRP when exposed to seawater and heat. This research investigates the influence of hygrothermal conditions on the physical and mechanical properties of GFRP. Samples were immersed in seawater at temperatures of 30°C, 40°C, and 60°C for 3 and 6 months. Results show that hygrothermal exposure leads to degradation in physical but notmechanical properties. Physical properties were evaluated using mass gain measurements, hardness testing, and Scanning Electron Microscopy (SEM), while mechanical properties were assessed via tensile testing.The result shown all specimen have increased mass up to 3,8% and decrease in hardnessup to 56%. SEM also shown several dark spot which indicatevoid. SEM analysis revealed the presence of dark spots, indicating void formation. These findings underscore the vulnerability of GFRP to hygrothermal conditions, raising concerns about its long-term durability in coastal applications.